L’apathique et l’esthétique. Réflexions sur les clausules du Nom de la rose et du Pendule de Foucault d’Umberto Eco - Piero Polidoro (Cahiers de Narratologie)
This article proposes a comparison between the final pages of Umberto Eco’s first two novels : The Name of the Rose and The Foucault’s Pendulum. In Eco’s work, the theoretical activity in semiotics and the writing of novels were narrowly intertwined and narration had a very special role because, as Eco himself used to say, « what you cannot theorize about, you must narrate ».Hence, in order to better understand this comparison, we need to analyze some aspects of Eco’s thought. The first aspect is his position about realism in philosophical debate ; he supported a specific form of realism, not naïve, which he called « negative ». The second aspect is his « reasonable » approach to theoretical discussion. This reasonableness is always linked to the research of an anchor point, a handhold, a clasp, on which to build the rest of the system. It is exactly the presence of this kind of clasp the difference between the finals of the two novels. In The Name of the Rose the lack of an order brings William to a complete defeat, which leaves him in a state of apathy. On the contrary, in The Foucault’s Pendulum, in a situation even more dramatic than William’s one, Casaubon finally find his serenity, his meaning, in an aesthetic dimension.